2015
DOI: 10.1051/0004-6361/201526338
|View full text |Cite
|
Sign up to set email alerts
|

AMBER-NACO aperture-synthesis imaging of the half-obscured central star and the edge-on disk of the red giant L2Puppis

Abstract: Aims. The red giant L 2 Pup started a dimming event in 1994, which is considered to be caused by the ejection of dust clouds. We present near-IR aperture-synthesis imaging of L 2 Pup achieved by combining data from VLT/NACO and the AMBER instrument of the Very Large Telescope Interferometer (VLTI). Our aim is to spatially resolve the innermost region of the circumstellar environment. Methods. We carried out speckle interferometric observations at 2.27 µm with VLT/NACO and long-baseline interferometric observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
2
14
1
Order By: Relevance
“…and the dust disk at a resolution corresponding to 0.9 AU at L 2 Pup. The east-west elongation of the diffuse emission is consistent with the major axis of the dust disk observed by Kervella et al (2014Kervella et al ( , 2015, Lykou et al (2015a,b), and Ohnaka et al (2015) at infrared and visible wavelengths. The visible image of L 2 Pup from Kervella et al (2015) is shown in Fig.…”
Section: Continuum Emissionsupporting
confidence: 88%
See 3 more Smart Citations
“…and the dust disk at a resolution corresponding to 0.9 AU at L 2 Pup. The east-west elongation of the diffuse emission is consistent with the major axis of the dust disk observed by Kervella et al (2014Kervella et al ( , 2015, Lykou et al (2015a,b), and Ohnaka et al (2015) at infrared and visible wavelengths. The visible image of L 2 Pup from Kervella et al (2015) is shown in Fig.…”
Section: Continuum Emissionsupporting
confidence: 88%
“…Ohnaka et al (2015) also concluded a high inclination from the partial obscuration of the stellar disk by the edge of the dust disk. We therefore adopt a value of i = 82 ± 5…”
Section: Mass Of the Central Objectmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, the presence of a disk has been inferred in a number of post-AGB objects (Bujarrabal et al 2013), while disks around AGB stars have remained elusive. However, clear evidence of a dust disk with an inner and outer edge lying at ≈ 6 and ≈ 13 au, respectively, has recently been found towards the M-star L 2 Pup Lykou et al 2015;Ohnaka et al 2015). This could be the first evidence of disk formation around a star at the end of its evolution on the AGB.…”
Section: Shaping Of Planetary Nebulaementioning
confidence: 83%